Redefining the Statute of Limitations in Document Forgery Cases: Implications for Legal Certainty and Criminal Investigations - Aprilianto, Sapta; Prihandono, Yoga; Nugraha, Xavier; Fuady, Muhammad Ikram Nur (Media Iuris, 2025)
The Constitutional Court Decision No. 118/PUU-XX/2022 redefined the paradigm of the statute of limitations for document forgery offenses in Indonesia. Previously calculated from the date of the offense, it is now determined based on when the forged document is discovered, used, and causes loss. This article examines the legal implications of the court decision on the state of limitations to legal certainty and law enforcement practices, particularly those carried out by the Indonesian National Police. A conceptual and statutory approach is employed to analyze the amendments to Article 79(1) of the Indonesian Criminal Code and the Court’s legal reasoning. The findings indicate that this change enhances legal protection for victims and requires investigators to cumulatively evaluate the elements of “discovery,” “usage,” and “loss” to determine the statute of limitations. The decision has erga omnes effect and serves as a binding precedent and guideline for investigating document forgery cases in Indonesia.